2021
DOI: 10.1590/1806-9282.20210686
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation as a preoperative risk factor predicts long-term mortality in elderly patients without heart failure and undergoing hip fracture surgery

Abstract: OBJECTIVE: Patients with atrial fibrillation (AF) constitute a significant portion of hip fracture patients, and both diseases tend to present more frequently in older age. Our goal was to evaluate the long-term mortality of patients with AF who were free from heart failure undergoing hip fracture surgery.METHODS: This observational, retrospective study was done in a single research and training hospital setting. Hospital electronic health record data, National Health Registry data, and National Death Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…43,44 Hip fractures are one of the most commonly occurring co-morbidities of chronic kidney diseases, 16,45,46 and are associated with poor prognostic outcomes in terms of short-, long-term morbidity and mortality, especially for patients undergoing hemodialysis. [47][48][49][50] Current studies suggest that this predisposition toward fractures is a result of increased parathyroid hormone levels and the disruption in calcium-phosphorus metabolism in chronic kidney disease patients. 51,52 Studies have also suggested a direct relationship between the incidences of fracture and the severity of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Hip fractures are one of the most commonly occurring co-morbidities of chronic kidney diseases, 16,45,46 and are associated with poor prognostic outcomes in terms of short-, long-term morbidity and mortality, especially for patients undergoing hemodialysis. [47][48][49][50] Current studies suggest that this predisposition toward fractures is a result of increased parathyroid hormone levels and the disruption in calcium-phosphorus metabolism in chronic kidney disease patients. 51,52 Studies have also suggested a direct relationship between the incidences of fracture and the severity of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“… 7 AF is the risk factor for in-hospital mortality and long-term mortality in elderly patients undergoing hip fracture surgery. 41 , 42 In our study, although POAF did not show an influence on mortality, it was associated with perioperative myocardial infarction, acute kidney injury, and complications, such as infection, fistula, and bleeding. Patients with AF had prolonged mechanical ventilation time, ICU, and hospital length of stay.…”
Section: Discussioncontrasting
confidence: 51%
“…Elderly patients with decreased physiological reserve and poor tolerance to fracture‐caused traumatic stress and who have undergone surgery might have higher perioperative risk. Old age has also been reported as an independent predictive factor for death in elderly patients with hip fractures 28 . Age is the main risk factor for death in elderly patients with femoral neck fractures at 30 days 29 and 1 year 30,31 after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Old age has also been reported as an independent predictive factor for death in elderly patients with hip fractures. 28 Age is the main risk factor for death in elderly patients with femoral neck fractures at 30 days 29 and 1 year 30,31 after surgery.…”
Section: Risk Factors Of Mortality After Artificial Hip Arthroplastymentioning
confidence: 99%